Moral distress of critical care nurses when initiating do-not-resuscitate orders for critical ill patients in a specific government hospital - Coetzee-Prinsloo, Isabel (University of Pretoria, 2023)
Dissertation (MA (Nursing Science))--University of Pretoria, 2023.